2015
DOI: 10.1038/nature14896
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for stop codon recognition in eukaryotes

Abstract: Termination of protein synthesis occurs when a translating ribosome encounters one of three universally conserved stop codons: UGA, UAA, or UAG. Release factors recognise stop codons in the ribosomal A site to mediate release of the nascent chain and recycling of the ribosome. Bacteria decode stop codons using two separate release factors with differing specificities for the second and third bases1. By contrast, eukaryotes rely on an evolutionarily unrelated omnipotent release factor (eRF1) to recognise all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
398
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(419 citation statements)
references
References 49 publications
21
398
0
Order By: Relevance
“…1 D-F), revealed that the absence of the methyl group was sufficient to enable A1824 to move in, whereas A1825 remained out (Fig. 2 C, F, and G), consistent with an eRF1-bound conformation (9) and termination at a PTC. Interestingly, the absence of the 6′ methyl group not only prevented steric blocking of A1824 but also allowed ring I to move partially below the backbone phosphates of the rRNA and make specific interactions that stabilized the "in" position (Fig.…”
Section: Significancementioning
confidence: 71%
See 1 more Smart Citation
“…1 D-F), revealed that the absence of the methyl group was sufficient to enable A1824 to move in, whereas A1825 remained out (Fig. 2 C, F, and G), consistent with an eRF1-bound conformation (9) and termination at a PTC. Interestingly, the absence of the 6′ methyl group not only prevented steric blocking of A1824 but also allowed ring I to move partially below the backbone phosphates of the rRNA and make specific interactions that stabilized the "in" position (Fig.…”
Section: Significancementioning
confidence: 71%
“…Critical to accurate codon recognition by both complexes is the conformation of A1824 and A1825, two conserved rRNA residues at helix 44 of the ribosome that can dynamically flip in and out of the helix. Structural studies have shown that binding of eRF1 flips A1825 out to facilitate stacking of termination codon bases and enable accurate recognition of the termination codon, whereas A1824 remains inside the helix (9). By contrast, A1825 and A1824 adopt a flipped-out conformation upon binding of a cognate tRNA complex, enabling them to interact with and stabilize the codon-anticodon duplex and ensuring fidelity of tRNA selection (10)(11)(12).…”
Section: Significancementioning
confidence: 99%
“…1A). The latter appeared because of the presence of a stop codon in the A-site, which is known to adopt a compact conformation leading to mRNA retraction into the A-site (31,32). This stop codon conformation is stabilised by eRF1, thus enhancing the 125 nt peak when it binds to the ribosome (30).…”
Section: Post Ribosomes Relocate Backwards By Three Nucleotides In Thmentioning
confidence: 99%
“…Generally, X-ray crystallography produces atomic-resolution structures (<~3 Å), while cryo-EM densities are resolved typically only at lower resolution (~5-30 Å). However, through recent developments in cryo-EM techniques, high-resolution (~2-5 Å) densities have been obtained [1, 2, 3, 4, 5]. Computational methods that combine information from crystallography and cryo-EM can bridge the resolution gap and hold the promise of generating physiologically accurate, atomic-resolution structures of biomolecular complexes.…”
Section: Introductionmentioning
confidence: 99%